2016
DOI: 10.1161/circulationaha.116.021114
|View full text |Cite
|
Sign up to set email alerts
|

Double Trouble

Abstract: ForewordInformation about a real patient is presented in stages (boldface type) to expert clinicians (Drs Ganame, Whitlock, Velianou, and Natarajan), who respond to the information, sharing their reasoning with the reader (regular type). A discussion by the authors follows. P atient presentation: A 29-year-old woman born in Canada, gravida 3, para 2 at 12 weeks gestation, presented to the cardiac pregnancy clinic with a 1-month history of progressive shortness of breath on exertion and chest discomfort. Her m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[ 8 ] There were case reports of transcatheter aortic valve implantation during pregnancy, but all were done through the femoral route. [ 9 10 ] Transfemoral, transatrial septal, and antegrade mitral valve implantation has been successfully tested in human trials using the CardiAQ transcatheter mitral valve (Edwards Lifesciences, Irvine, CA, USA), but it was not commercially available. [ 11 ] Decision to deploy both Edwards Sapien XT valves through the LV apical approach was taken because this valve can be deployed in mitral position only through this approach and this is a standardized alternative route for its deployment in the aortic position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] There were case reports of transcatheter aortic valve implantation during pregnancy, but all were done through the femoral route. [ 9 10 ] Transfemoral, transatrial septal, and antegrade mitral valve implantation has been successfully tested in human trials using the CardiAQ transcatheter mitral valve (Edwards Lifesciences, Irvine, CA, USA), but it was not commercially available. [ 11 ] Decision to deploy both Edwards Sapien XT valves through the LV apical approach was taken because this valve can be deployed in mitral position only through this approach and this is a standardized alternative route for its deployment in the aortic position.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Strategies to minimize radiation exposure are avoidance of unnecessary radiological investigations, use of appropriate radiation shields, avoid/restrict cineradiography, and minimize the total duration and amount of radiation by depending more on fluorography and fluoro-grab at a lower frame rate and “LOW” power setting. [ 10 ] A computed tomographic (CT) angiogram could be avoided in this patient because the in situ prosthetic valve sizes were known and the planned approach was through the LV apex. A transfemoral approach requires a CT angiographic scan to assess the size and nature of femoral arteries, iliac arteries, and aorta and mandates fluoroscopic guidance while advancing guidewires, catheters, and valve assembly through these vessels during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had infective endocarditis secondary to the fibrosed aortic valve, which is very rare but lethal to both the mother and fetus [ 11 ]. The patient, in this case, had the emergent cesarean section followed by successful replacement of aortic valve which helped reduce the risk of mortality in both the mother and the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published literature on AVR during pregnancy was all in the pre-viable period, due to the inability to deliver even a pre-viable fetus in conjunction with the inability to further delay cardiac surgery based on maternal status ( Table 1 ). 5 , 6 , 7 , 8 , 9 However, preterm delivery even after viability may still carry significant neonatal morbidity and mortality and, if able to be avoided, is strongly preferred. Orwat et al 3 found that the peak aortic gradient before pregnancy as a continuous variable was the only independent predictor of complications.…”
Section: Question 4: At What Symptom or Mean Gradient Threshold Shoul...mentioning
confidence: 99%